Protective Strategies for the Ownership of Traditional Medicine Knowledge - Zainul Daulay1 , Kurnia Warman2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This paper discusses the ownership of traditional medicine knowledge by drawing empirical data on theexperience of the indigenous communities in Mentawai, Indonesia, and Sabah, Malaysia. For a long time,the acquisition of traditional medicine knowledge and the treatment of patients has been deemed the resultof cultural heritage handed down from generation to generation. However, the complexity of the knowledgeacquisition process and the skill displayed by the healer or kerei prove that traditional medicine knowledgequalifies as intellectual property. An appropriate protection strategy is identified based on the traditionalknowledge ownership map in indigenous communities. This study reveals that not every traditional medicineknowledge and practices are “common properties”. Therefore, the study suggests that traditional medicineknowledge, like any other intellectual properties, must be protected through intellectual property rights notonly to protect the cultural and economic rights of indigenous people but also to protect the environment.